2017
DOI: 10.1002/slct.201701012
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Fluorescent Carbon Dots for Ratiometric Intracellular pH Sensing

Abstract: We report here carbon dots (CDs) that can be utilized for intracellular pH sensing via fluorescence emission monitoring. The carbon dots are synthesized using a simple procedure from an economical carbon source Agaricus bisporus. Along with the excitation dependent fluorescence emission, typical to carbon dots, these CDs were found to have distinct emission maxima peaks at 450 nm and 550 nm when excited by 365 nm and 500 nm respectively. Interestingly, while the fluorescence emission at 450 nm was unaffected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The luminescence of carbon dots is susceptible to PET quenching making ion sensing possible in principle . Because of the low cytotoxicity, intracellular pH-imaging represents one of the major applications. …”
Section: Nanomaterialsmentioning
confidence: 99%
“…The luminescence of carbon dots is susceptible to PET quenching making ion sensing possible in principle . Because of the low cytotoxicity, intracellular pH-imaging represents one of the major applications. …”
Section: Nanomaterialsmentioning
confidence: 99%
“…From the fluorescence intensity at the two aforementioned wavelengths, and by using the ratiometric calibration curve, they calculated the pH of the cell, besides observing the different color of the cells. Likewise, Chandra et al developed CNDs from the mushroom Agaricus bisporus and ethylenediamine and they found that the CNDs can detect changes in the intracellular pH of HeLa cells [89]. Their CNDs exhibit dual emission, one at 450 nm and one at 550 nm.…”
Section: Target-specific Imaging Applications For Eukaryotic Cellsmentioning
confidence: 99%
“…[38] Among carbon-based fluorescent nanomaterials, pH sensors derived from graphene quantum dots [39][40][41][42] and carbon dots are common. [43][44][45][46] Their exquisite fluorescence properties make them very advantageous in many aspects, however they have a tendency to interact with cellular mechanisms and thus can interfere with the studies in question.…”
Section: Introductionmentioning
confidence: 99%